Predictive Value of FOLFOX-Based Regimen, Long Interval, Hemoglobin Levels and Clinical Negative Nodal Status, and Postchemoradiotherapy CEA Levels for Pathological Complete Response in Patients with Locally Advanced Rectal Cancer after Neoadjuvant Chemoradiotherapy. (28th January 2020) - Huang, Chun-Ming; Huang, Ching-Wen; Ma, Cheng-Jen; Yeh, Yung-Sung; Su, Wei-Chih; Chang, Tsung-Kun; Tsai, Hsiang-Lin; Juo, Suh-Hang; Huang, Ming-Yii; Wang, Jaw-Yuan
Abstract : We aimed to identify predictors of a pathological complete response (pCR) in patients with locally advanced rectal cancer (LARC) following a multimodality therapy. We retrospectively reviewed 236 patients with LARC treated with neoadjuvant chemoradiotherapy (CRT) followed by radical resection from January 2011 to December 2017. Patients were administered CRT, which comprised radiotherapy and chemotherapy with an oxaliplatin plus 5-fluorouracil- or fluoropyrimidine-based regimen. Clinical factors were correlated with treatment response. The multivariate logistic regression revealed that a negative nodal stage (odds ratio (OR) = 3.2, P = 0.0135 ), a high hemoglobin level (>10 g/dL) during neoadjuvant CRT (OR = 3.067, P = 0.0125 ), an oxaliplatin-containing neoadjuvant CRT (OR = 5.385, P = 0.0044 ), a long interval (>8 weeks) between radiotherapy and surgery (OR = 1.135, P = 0.0469 ), and a post-CRT CEA ≤2 ng/mL (OR = 2.891, P = 0.0233 ) were the independent predictors of increased pCR rates. The prediction nomogram was developed according to the above independent variables. The concordance index was 0.74, and the calibration curve showed good agreement. In summary, negative nodal stages, high hemoglobin levels during treatment, oxaliplatin-containing neoadjuvant therapy, a long radiotherapy-surgery interval (>8 weeks), and post-CRT CEA levels ≤2 ng/mL were favorable predictors of a pCR. This prediction nomogram might be crucial for patients with LARC undergoing a multimodality therapy.